Global Entrepreneurship and Development Index 2015 - Acs, Zoltan J.; Szerb, László; Autio, Erkko (SpringerBriefs in Economics,, 2016)
This volume provides a detailed look at the entrepreneurial ecosystem of different nations by combining individual data with institutional components. The composite index presented in this book, the Global Entrepreneurship Index (GEI), aims to measure the quality and scale of the entrepreneurial process in 130 countries around the world. The authors have developed a system that links institutions and agents through a National Entrepreneurial System (ecosystem) in which each biotic and abiotic component is reinforced by the other at a country level. The enclosed data, from both individual- and country-level institutions, provides policymakers a tool for understanding the entrepreneurial strengths and weaknesses of their respective economies, thereby enabling the implementation of policies that foster productive entrepreneurship. Distinct from both output-based entrepreneurship indexes (i.e., new firm counts) and process-based indexes (i.e., comparisons of policies and regulations), the GEI is designed to profile national systems of entrepreneurship. The GEI is a construction of individual and institutional measures that integrates 31 variables from various data sources into 14 pillars, three sub-indexes and a 'super index'. The relationship between entrepreneurship and economic development appears to be more or less mildly S-shaped. The findings suggest moving away from simple measures of entrepreneurship across countries illustrating a U-shaped or L-shaped relationship to more complex measures, which are positively related to development. The Index also does not focus exclusively on high-growth entrepreneurship; it also considers the characteristics of entrepreneurship that enhance productivity: innovation, market expansion, being growth oriented, and having an international outlook. Moreover, because entrepreneurship can have both economic and social consequences for the individual, the GEI captures the dynamic, institutionally embedded interactions between the individual-level attitudes, abilities, and aspirations that drive productive entrepreneurship. This unique book will be invaluable for researchers, policymakers and entrepreneurs keen to expand their understanding of entrepreneurship and development.